2015
DOI: 10.1177/0840470415581257
|View full text |Cite
|
Sign up to set email alerts
|

A protocol to reduce police wait times in the emergency department

Abstract: Healthcare organizations are increasingly tasked with implementing change initiatives that improve the patient experience and target priorities such as Emergency Department (ED) volumes. This article describes the development, implementation, and outcomes of a collaborative protocol between the Niagara Health System and the Niagara Regional Police Service that resulted in a 57% reduction in police wait times in the ED. Six critical success factors contributed to the outcomes that were achieved and are detailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The target audience for the CMH is also adults aged 18 years and older, including a broad range of service recipients. Although community mental health agencies are the typical service provider, it has been used in consultation liaison services for long-term care to deal with psychiatric and behavioral issues outside the usual scope of practice for clinicians in those settings as well as a Dutch study of homeless services recipients (162). The original version of the CMH released in 2007 was pilot tested in Ontario, Canada, New York State, Finland, Belgium, Chile and Hong Kong.…”
Section: Community Mental Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…The target audience for the CMH is also adults aged 18 years and older, including a broad range of service recipients. Although community mental health agencies are the typical service provider, it has been used in consultation liaison services for long-term care to deal with psychiatric and behavioral issues outside the usual scope of practice for clinicians in those settings as well as a Dutch study of homeless services recipients (162). The original version of the CMH released in 2007 was pilot tested in Ontario, Canada, New York State, Finland, Belgium, Chile and Hong Kong.…”
Section: Community Mental Healthmentioning
confidence: 99%
“…For this paper, 12,862 assessments from pilot studies are available for analyses. Because of constraints related to European data protection laws, it was not possible to complete pooled analyses with those data (162). The CMH includes 405 items dealing with comparable domains and look-back periods as used in the MH.…”
Section: Community Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only a handful of temporal studies exist in this domain with most publications focusing on the duration of calls-for-service and often within the context of some form of program evaluation (Heslin et al, 2017;Pizzingrilli, Hoffman, & Hirdes, 2015;Redondo & Currier, 2003;Szkopek-Szkopowski et al, 2013). In this paper, we contribute to the temporal study of police activity through an investigation of police calls for service that relate to the Mental Health Act (herein referred to as MHA) in British Columbia.…”
Section: Introductionmentioning
confidence: 99%
“…For example, officers with the Vancouver Police Department wait an average of 1 hour and 11 minutes on calls related to a PMI and can wait up to five hours in some instances (Thompson, 2010). In another Canadian study, researchers found police officers waited an average of four hours in the emergency department on calls related to PMIs (Pizzingrilli et al, 2015). Because of these extensive wait times, some hospitals in Ontario have initiated inter-agency agreements with local police services in attempts to reduce wait-times associated with apprehended PMIs (PHSJCC, 2011).…”
Section: Mental Illness and The Criminal Justice Systemmentioning
confidence: 99%